Framing Analysis of Ferry Irwandi's YouTube Content on the Mastermind of the Riots and the Discourse of Martial Law - Rahmat Edi Irawan (representamen, 2025)
This study aims to analyze how framing is constructed through Ferry Irwandi’s YouTube account regarding the mastermind of the August 2025 riots and the discourse on the implementation of martial law in Indonesia. The study employs a qualitative approach using Robert N. Entman’s framing analysis model, which emphasizes four main elements: problem definition, causal interpretation, moral evaluation, and treatment recommendation. Data were obtained from the transcription of video content uploaded on Ferry Irwandi’s YouTube channel during the August–September 2025 period and were then analyzed in depth to reveal the construction of meaning. The findings show that the framing built by Ferry Irwandi tends to highlight certain political actors as the masterminds behind the riots, frames the riots as a threat to state stability, and directs public opinion toward supporting the implementation of martial law by the TNI. These findings suggest that the content serves not only as an information channel but also as a tool for shaping public opinion. This study is expected to contribute to the field of political communication studies, particularly in understanding the role of media framing in shaping public opinion on emerging political issues in the public sphere. Keywords: Framing Analysis, YouTube Content, Political Issues, Riots, Martial Law